A 2-year clinical evaluation of direct and semi-direct resin composite restorations in non-carious cervical lesions: a randomized clinical study - Caneppele, Taciana Marco Ferraz [UNESP]; Meirelles, Laura Célia Fernandes [UNESP]; Rocha, Rafael Santos [UNESP]; Gonçalves, Lucélia Lemes [UNESP]; Ávila, Daniele Mara Silva [UNESP]; Gonçalves, Sérgio Eduardo de Paiva [UNESP]; Bresciani, Eduardo [UNESP] (Springer Nature, 2019)
Objectives: The purpose of this study was to evaluate the 2-year success of resin composite restorations in non-carious cervical lesions (NCCLs) using the direct or semi-direct techniques. Materials and methods: Thirty volunteers presenting with at least two NCCLs were included. Each participant received one restoration using the direct technique and the other using the semi-direct technique, totaling 60 restorations. Time for completing the treatment was computed. Assessments at baseline, 7 days, and 6, 12, and 24 months were performed using the modified United States Public Health Service criteria. Descriptive analysis was reported as a percentage of successful treatments. For inferential analysis, the Student t test was used to evaluate the differences between extension, depth, and time. The chi-square/Fisher tests were used to compare treatment success after each period (α = 0.05). The results were evaluated by using the Kaplan-Meier survival analysis. Results: Differences were detected regarding mean ± standard deviation time, in which direct and semi-direct procedures were accomplished in 21.8 (± 14.5) and 35.3 (± 19.9) min, respectively. Of the 60 restorations placed, 7 failed in the direct group while 8 failed in the semi-direct group up to 2 years. No differences were detected between restorative protocols. The cumulative survival was 88.5% and 88.4% for the direct technique and semi-direct techniques after 24 months, respectively. Conclusion: The tested restorative protocols present similar results for NCCLs within the studied periods. Clinical relevance: The semi-direct technique exhibited clinical performance similar to direct technique for NCCL, demonstrating an alternative for restorations of these lesions.
Keywords: Composite resin; Non-carious cervical lesions; Randomized clinical trial; Semi-direct technique